TELOS Feasibility Evaluation of the e-HakCipta System: Evidence from Intellectual Property Centers in Samarinda - Reza Andrea; Sari Armiati; Tri Hannanto Saputra; Agustinus Fritz Wijaya; Aulia Khoirunnita; Suswanto; Hermawati (Journal of Information System and Informatics, 2026)
This study evaluates the feasibility of the updated e-HakCipta system developed by the Directorate General of Intellectual Property (DJKI), Ministry of Law and Human Rights, based on user perceptions at Intellectual Property Centers (Sentra KI) in Samarinda. A descriptive quantitative approach was employed using a structured Likert-scale questionnaire validated by three domain experts. Data were collected from seven participating institutions, each represented by one designated e-HakCipta user. The evaluation applied the TELOS framework, covering Technological, Economic, Legal, Operational, and Schedule feasibility. The results show that all dimensions exceeded the feasibility threshold. Economic feasibility achieved the highest mean score (4.33), followed by Schedule (3.90), Technological (3.86), Operational (3.76), and Legal feasibility (3.67). The overall TELOS composite score of 3.90 indicates that the system is feasible. These findings suggest that the updated e-HakCipta system improves cost efficiency, registration speed, and interface usability, although legal compliance verification, plagiarism detection, and system stability require further enhancement.